Back Cover: A Modular Approach to Inorganic Phosphazane Macrocycles (Angew. Chem. Int. Ed. 31/2017). Issue 31 (20th June 2017) - Plajer, Alex J.; García‐Rodríguez, Raúl; Benson, Callum G. M.; Matthews, Peter D.; Bond, Andrew D.; Singh, Sanjay; Gade, Lutz H.; Wright, Dominic S.
Abstract : The union of organic and macrocyclic chemistry : The formation of large inorganic macrocycles containing phosphazane units linked by sulfur or selenium becomes straightforward with the method described by D. S. Wright et al. in their Communication onpage 9087 ff. This allows the introduction of a range of organic substituents, facilitating the tuning of the steric and electronic host environment, and marks a significant step towards the development of synthetic tools in macromolecular inorganic assembly that mirror those in organic synthesis.